Ragam Tipomorfologi Beserta Fungsi Pengerasak di Kecamatan Penebel Tabanan Bali - Deo Agung Prakoso; I Bagus Gede Bhujangga Hardina Putra (Badan Riset dan Inovasi Nasional (BRIN), 2022)
Stone throne or Pengerasak as the local community in Rejasa Tabanan district said, is a medium to ask for a blessing to the creator for their agricultural harvest and for avoiding disaster. This research aimed to understand the development of pengerasak's shape and its function which are still preserved until today. Ethnoarcheology and analytical typo-morphology approach was carried out in order to solve the questions in this research, which was done through field survey and interview in three villages, those are Rejasa, Pesagi and Tegallinggah Villages, in Penebel District. The collected data then presented in descriptive analytic to solve the question that has the connection with the shape of the remain of Pengerasak along with the religious rites. The shape of pengerasak can be divided into three, there are the basic shape, the one with the armrest shape, and terraced shape. Based on its placement it has similarities with the stone thrones from the megalithical culture era and has the same function with Hindu's Palinggih as the place to enthrone (stana) God in Hinduism. Pengerasak placed in a fertile land such as rice field and orchard, each has its own rituals. Thus, it's hope for a balance in the utilization of natural resources.